ASSOCIATION BETWEEN THE USE OF CANNABIS AND DEPRESSION IN UNITED STATES ADULTS - ORTIZ ARAUJO, KATHERINE JOHANNA (2023)
Recent studies show a growing body of evidence suggesting that users of cannabis have consistently higher prevalence rates of depressive disorders in comparison to non-users. Besides, it can be used as a highly effective treatment for depression and other mood disorders. A study with a cross-sectional design was conducted with data from respondents aged 25-64 who participated in the 2018 Behavioral Risk Factor Surveillance System (BRFSS) survey. The population was assessed for the baseline characteristics, followed by a bivariate analysis, a multivariate logistic regression to control any confounders, and assess the association between the use of cannabis and depression. The sample included 57,757 individuals. The unadjusted binary logistic regression indicated that those who use cannabis are 93% more likely (OR: 1.93) to have a diagnosis of depression. On the other hand, the adjusted analysis indicated that those who use cannabis are 78% more likely (OR: 1.78) to have a diagnosis of depression. Other variables including participants under the age of 45 years were significantly associated with the diagnosis of depression (OR: 1.35). Moreover, participants with an education without a high school diploma (OR: 0.54), and those having a full-time commitment (OR: 0.37) were significantly less likely to have a diagnosis of depression. Findings suggest that selected U.S. participants who use cannabis have an increased risk to report depression. Furthermore, factors such as age, level of education, and a person’s time commitment status were found to have a significant influence on whether a diagnosis of depression is present.